Synthesis of silver nanoparticles from Pseudophegopteris microstegia (Hook.) Ching and their biological activities against tomato gray mold - Iraj Mushtaq; Sadaf Kayani; Tijen Demiral Sert; Qaisar Abbas Bhatti; Muhammad Zeeshan Qureshi; Hu Shubao; Kamran Iqbal Shinwari (Journal of Agriculture and Food Research)
For the first time, the unexplored fern Pseudophegopteris microstegia (Hook.) Ching (P. microstegia) was used to synthesize silver nanoparticles (AgNPs). Its leaves methanolic extract (Pm) was evaluated for distinct phytochemicals with significant antioxidant capacity, reducing power, and free radical scavenging features. As a distinctive approach, the present study designated the biosynthesis, characterization, and bioactivities of the PmAgNPs (P. microstegia-mediated AgNPs) via different techniques. In the UV–vis spectrum, the maximum absorption peak at 431 nm confirmed the formation of AgNPs. In contrast, the FTIR spectrum uncovered the involvement of phytoconstituents of different functional groups as reducing and capping agents in PmAgNPs synthesis. XRD analysis confirmed the crystalline structure and SEM/TEM captured the clustered spherical-shaped micrographs of nanoparticles with diameters ranging from 30 to 40 nm. The antibacterial and antifungal activities of the PmAgNPs (and at concentration: 100 μg/μL) were significantly enhanced compared to the Pm. The PmAgNPs treatment produced the maximum zone of inhibition of 23.4 mm against the bacterium Acinetobacter baumannii and 18.8 mm against the fungus Botrytis cinerea. In a pot experiment in tomato plants, applying PmAgNPs solution against B. cinerea infection unveiled that these have a biocontrol protection efficiency of nearly 55–60 % by reducing infection lesions on leaves and fruits. The analysis of tomato stress response indicators such as proline, total soluble sugars, antioxidant contents, and lipid peroxidation showed that PmAgNPs application protected against harmful B. cinerea stress. Our exclusive findings concluded that P. microstegia holds medicinal value, and its green synthesized PmAgNPs might serve as potentially therapeutic, antimicrobial, and antifungal (biocontrol) agents.